Hierarchical porous Co(OH)F/Ni(OH)2: A new hybrid for supercapacitors. (1st March 2018) - Li, Xudong; Ding, Rui; Shi, Wei; Xu, Qilei; Ying, Danfeng; Huang, Yongfa; Liu, Enhui
Abstract: A new hybrid hierarchical porous Co(OH)F/Ni(OH)2 for supercapacitors was fabricated via one-pot hydrothermal method. X-ray diffraction (XRD) revealed that the Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) hybrid was composed of orthorhombic Co(OH)F and hexagonal Ni(OH)2 phases. X-ray photoelectron spectra (XPS) illustrated the presence of O1s, F1s, Co2p and Ni2p for the Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) hybrid. The scanning/transmission electron microscopy (SEM/TEM) showed that the Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) hybrid exhibited the morphology of both the nanorods of bare Co(OH)F and nanoflakes of bare Ni(OH)2 . The energy dispersive spectrometry (EDS) and mapping results showed the Co/Ni ratio of 3.1:1 and uniform distributions of O, F, Co and Ni elements of the Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) hybrid. Nitrogen sorption measurements suggest the hierarchical porous structure of the Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) hybrid. The Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) hybrid showed the more attractive electrochemical performance than the other Co(OH)F/Ni(OH)2 candidates (Co/Ni = 1:0, 1:1, 1:3, 0:1) due to the stronger synergistic effect of Co and Ni redox species, exhibiting high specific capacity and rate behavior (104-98 C g −1  at 1–16 A g −1 ) together with excellent cycling stability (116% retention/5000 cycles/6 A g −1 ). Furthermore, the designed activated carbon (AC)//Co(OH)F/Ni(OH)2 (Co/Ni = 3:1) asymmetric capacitor exported both high energy and power densities (13.8–8 Wh kg −1 /0.53–4.7 kW kg −1 ) along with excellent cycle life (121% retention/10, 000 cycles/4 A g −1 ), showing the superior performance than the other AC//Co(OH)F/Ni(OH)2 capacitors (Co/Ni = 1:0, 1:1, 1:3, 0:1).